Penal Mediation in Settlement of Copyright Crimes in Indonesia - Muhammad Saiful Fahmi,; Rudini Hasyim Rado,; Mulyadi Alrianto Tajuddin,; Nurul Widhanita Y. Badilla,; Ricardo Goncalves Klau, (Technium Social Sciences Journal, 2023)
This study aims to obtain an overview of Penal Mediation in the Settlement of Copyright Crimes in Indonesia. The research method uses a normative juridical approach, type of data uses qualitative data and data sources in the form of secondary data, data collection methods using literature study methods, and documentation. Furthermore, the data will be analyzed qualitatively and then conclusions will be conclused with deductive approach. In the provisions of Article 95 of Law Number 28 of 2014 concerning Copyright henceforward referred to as the Copyright Law, the government has given options to the parties in resolving disputes, namely by Alternative Dispute Resolution, Arbitration, and Court Institutions. The implementation of this mediation is known as penal mediation. Penal mediation pursued in the event of misdemeanor offenses and cases of a delict nature. The imposition of criminal law related to copyright infringement that requires mediation in advance in addition to piracy follows the function of criminal law as an ultimum remedium which is the last resort if other laws cannot provide a solution, however, for criminal acts of piracy, mediation is not carried out (penal mediation) but directly by using the litigation mechanism in this case the district court.